2017
DOI: 10.1016/j.adro.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported distress and survival among patients receiving definitive radiation therapy

Abstract: ObjectivePatient-reported distress (PRD) has not been well assessed in association with survival after radiation therapy (RT). The aims of this study were to evaluate the association between PRD level and survival after definitive RT and to identify the main causes of distress in definitive RT patients.Methods and materialsA total of 678 consecutive patients receiving definitive RT at our institution from April 2012 through May 2015 were included. All patients answered a PRD questionnaire that contained 30 ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…Given the negative survival sequelae associated with distress in the HNC population and that mask anxiety is a well–identified contributor to distress, it is essential for patient care that cancer centres have an understanding of mask anxiety with the HNC population receiving RT . Our study is first to report the longitudinal severity and course of mask anxiety during RT for HNC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the negative survival sequelae associated with distress in the HNC population and that mask anxiety is a well–identified contributor to distress, it is essential for patient care that cancer centres have an understanding of mask anxiety with the HNC population receiving RT . Our study is first to report the longitudinal severity and course of mask anxiety during RT for HNC.…”
Section: Discussionmentioning
confidence: 99%
“…Distress is a term that has been adopted to describe an unpleasant experience of a psychological, social, spiritual and/or physical nature . In the population with HNC, patient–reported distress before and after radiotherapy (RT) is prognostic for poorer survival, with long–term challenges associated with physical functioning, fatigue and reduced social supports contributing to distress . Furthermore, distress in the population with HNC has been found to be related to the use of the thermoplastic mask required to immobilise patients to ensure precision of RT treatment …”
Section: Introductionmentioning
confidence: 99%
“…One study found that high distress levels measured before and during radiation therapy (RT) prognostic with higher distress levels associated with decreased survival. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been made to correlate distress with specific cancer outcomes. One study found that high distress levels measured before and during radiation therapy (RT) prognostic with higher distress levels associated with decreased survival 9 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 All of these factors have the potential of increasing patient distress, and this has been shown to lead to decreased survival following cancer therapy. 4 What can medical physicists do to help? We are uniquely positioned to serve as an information resource for patients during a formalized meeting at the initial consult.…”
mentioning
confidence: 99%